Dinamika Pemanfaatan Ruang Berbasis Kearifan Lokal di Kabupaten Buleleng Provinsi Bali - I Gede Astra Wesnawa (Forum Geografi, 2010)
This Research is carried out in urban area and countryside of Buleleng regency. Generally, the aim of this study is to analyze the dynamic space exploitation based on local wisdom. Particularly. this research aims to: (1) analyze the difference of applying of local wise aspect in exploiting of regional room of countryside and lawn of custom society house in urban area and countryside, and factors that cause the difference of its applying and (2) solution of using custom countryside room and lawn of custom society house in urban area and countryside based on local wisdom. To reach the target designed research by using survey device, by using household as analysis unit. Household Sample is determined by proportional sampling random (145 sample). Data are collected through documentation technique, and interview of questioner. Then the data analyzed are through technique analyze qualitative. Research result out find differences of local wisdom applying in exploiting of regional room of countryside and lawn of house, and solution in exploiting of room base on local wisdom concept as materialization of human being interaction process with environment. Based on the research result, contribution that can be put forward: (1) contribution of theory: approach of countryside scale spatial and house made excellence of this research to express the difference of local wise applying in exploiting of regional room of countryside and lawn of house and (2) practical contribution: exploiting of room based on local wisdom can survive and sustain to influence modernize if custom society remains to tie with custom countryside. The concept of Tri Hita Karana as form of local wisdom form in utilizing adaptive room against change and growth of an era which is indicated with being compromise on Kahyangan Tiga as a soul of dwelling, territorial area as a village physical form and people who dwell there. This harmonious relation guarantee harmonious preserving environment.